Քաղաքական ընդդիմության ինստիտուտի առանձնահատկությունները տարբեր մշակութային միջավայրերում - Գ . Վ . Մխոյան (ՀՀ ԳԱԱ հրատ.)
Изучение института политической оппозиции в разных культурных средах играет важную роль для характеристики этого явления. The study of political opposition institute in different cultural environments has an important role for the characterization of the political opposition.
Keywords: Political Science; J Political Science; Political institutions